Survival Rate and Prognostic Factors among Iranian Breast Cancer Patients - Mojtaba MESHKAT; Ahmad Reza BAGHESTANI; Farid ZAYERI; Maryam KHAYAMZADEH; Mohammad Esmaeil AKBARI (Tehran University of Medical Sciences, 2020)
Background: Survival time is one of the indicators used for evaluation of the quality of care in different types of malignancies, including breast cancer. The present study aimed to estimate the survival rate of breast cancer and its related factors among Iranian patients. Methods: Overall, 3148 cases of breast cancer who referred to the Cancer Research Center in Shahid Beheshti University of Medical Sciences, Tehran, Iran during 1994-2017 participated in this longitudinal study. Survival estimates were calculated using the Kaplan-Meier method and the Bayesian generalized Birnbaum-Saunders model with cure rate from geometric distribution. Clinical, pathological, and biological variables as potential prognostic factors were entered in univariate and multivariate analyses. In order to identify the significant prognostic factors, 95% highest posterior density (HPD) intervals were used. Results: The overall 1, 5, 10, 15, 20 and 25-year survival rate were 95%, 75%, 60%, 47%, 46% and 46%, respectively. A significant relation was observed between survival time and the variables such as age, size of tumor, number of lymph nodes, stage, histological grade, estrogen receptor, progesterone receptor, and lymphovascular invasion. Conclusion: The findings of this study might help the health managers to plan long-term programs considering regional determinants, public education, and screening for early detection of breast cancer cases which can eventually influence the overall survival rate of these patients.